PERANAN HUMAS DALAM MERESPON KONFLIK INTERNAL PADA UNIVERSITAS SAM RATULANGI MANADO - Rettobjaan, Imelda (ACTA DIURNA KOMUNIKASI, 2013)
The role of mass communication to respond the internal conflict in Sam Ratulangi University is derived on inventarising the problems consisted of how to back again the good image for the university and how to make an approach based on the persuasive communication and to wire out the miss communication. Keywords : mass communication, conflict, good image.